Mapping Visualization Analysis of Computer Science Research data in 2017-2021 on the Google Scholar database with VOSviewer - Al Husaeni, Dwi Fitria; Nandiyanto, Asep Bayu Dani (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
The purpose of this research is to examine the development and interrelationships between terms in computer science research using mapping analysis with VOSviewer. The research data was collected from the Google Scholar database for the period 2017-2021 using the Publish or Perish 7 application. Data collection was based on the keyword "Computer Science". The data search results found 992 articles that were considered relevant. The results showed that computer science research experienced high popularity in 2018 with a total of 232 articles. Computer science research experienced a decline in research in 2019-2021. Based on the mapping analysis that has been done using the VOSviewer application, computer science terms are connected to 4 main terms in each cluster, namely student, computer science education, education, and skills. Computer science research is mostly associated with the term student, namely the strength of link 221. This research can be used as a reference in determining the research theme or research discussion topic in the field of computer science.